The effect of culture on attitude towards online advertising and online brands: applying hofstede's cultural factors to internet marketing - Valaei, Naser (Inderscience Enterprises Ltd., 2016)
In formulating advertising and marketing strategies , marketers usually ignore cultural values at their peril. Little is known about the effects of national culture on individuals' att itude towards online advertising and brands. The pu rpose of this study is to examine Hofstede's cultural factors including indiv idualism, uncertainty avoidance, power distance, ma sculinity and femininity, and long-term orientation on Attitude towards Onlin e Advertisements (ATOA) and Attitude towards Online Brands (ATOB). Structural equation modelling was employed using pa rtial least squares path modelling analysis to empi rically test the proposed research model using 258 valid online ques tionnaires for evaluation of measurement and struct ural model for reflective constructs. The results indicate that in dividualism and long-term orientation are predictor s of ATOA and ATOB. In addition, uncertainty avoidance does not have a pos itive relationship with ATOA and ATOB. The hypothes is on masculinity and ATOA is rejected, while there is no association bet ween power distance and ATOB. Contribution of the s tudy, limitations and further directions are proposed for future studies.